Sakinah Resilien dalam Qs. Ar-Rum [30]:21: Rekonstruksi Makna Keluarga Sakinah Melalui Pendekatan Tafsir Maqāṣidi - Fadwa Nabilah; Ahmad Nurrohim (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2026)
The phenomenon of the modern domestic crisis, triggered by digital disruption, shifting social roles, and increasing mental health vulnerabilities, calls for a reorientation in our understanding of the concept of sakinah. Traditional interpretations, which tend to define sakinah as a descriptive state of tranquillity, often fall short in addressing the dynamics of contemporary relational conflicts. This study aims to reconstruct the meaning of sakinah in QS. Ar-Rūm [30]: 21 through a maqāṣidi exegetical approach. The method employed is a literature review with qualitative analysis of exegetical texts and the modern social context. The findings indicate that sakinah is not merely understood as emotional tranquillity, but as a relational mechanism that serves to preserve the stability of the soul (ḥifẓ al-nafs) and the continuity of the lineage (ḥifẓ al-nasl). This study proposes the concept of resilient sakinah, namely the interpretation of sakinah as an adaptive capacity in managing conflict in a ma‘rūf manner. Thus, sakinah is not measured by the absence of conflict, but by the ability to maintain relationships oriented towards the common good.